PERANCANGAN SISTEM PENGELOLAAN DATA PEMELIHARAAN SARANA DAN PRASARANA PADA YAYASAN SAYAP IBU BINTARO BERBASIS JAVA - Taopik Kusdinar; Rifki Ristiawan (Jurnal Manajamen Informatika Jayakarta, 2023)
The Sayap Ibu Foundation, Banten Province Branch, also known as the Sayap Ibu Bintaro Foundation, is a non-profit organization which was inaugurated on October 1, 2015, located at Graha Bintaro, South Tangerang, which is a development of the Sayap Ibu Foundation. In collaborating or partnering with the Sayap Ibu Bintaro Foundation, both institutions, companies and others, problems and obstacles often occur which make it difficult for the Sayap Ibu Bintaro Foundation to handle them. The usual problem that is often encountered is an error in recording partner data in carrying out maintenance of facilities and infrastructure and others. In this study the authors used a type of qualitative method, namely the method of fact finding techniques. Fact finding is a formal process of using techniques such as interviews and questionnaires to gather facts about systems, requirements, and options. The purpose of this research is to find out the data management process activities for the maintenance of facilities and infrastructure as well as partner data, in order to obtain accurate data according to the needs of the Foundation. The problems found at the Sayap Ibu Bintaro Foundation required computerized information technology. Computers help speed up data processing and employees in recording (input) data quickly and accurately. So that in the process of recording data neatly arranged. This can be considered as a positive thing as long as it is responsible and does not harm other parties in carrying out their work activities. With system facilities that use computers, foundations can search for and access various kinds of information. Application Data management system for maintenance of facilities and infrastructure is created with the support of the Java programming language, Netbeans 8.2, XAMPP, and the MYSQL database.. Keywords: Data Processing, Facilities and Infrastructure, Netbeans 8.2, Java, MySQL.